Efficacy of vitamin E in oral submucous fibrosis: A clinical and histopathologic study - Venkateswarlu Nallapu; Bhavya Balasankulu; Hima Bindu Vuppalapati; Sailaja Sambhana; Dayanandam Mala; Sri Krishna Koppula (Wolters Kluwer Medknow Publications, 2015)
Introduction: Oral submucous fibrosis is a scarring progressive disease characterized by juxta-epithelial inflammatory reaction and progressive fibrosis of the submucosal tissues, i.e., lamina propria and deeper connective tissues. An attempt was made in this study to evaluate the role of vitamin E in the treatment of oral submucous fibrosis by carrying out a comparative study between regular intralesional dexamethasone, hyaluronidase, and local anesthesia with and without oral vitamin E capsules. Materials and Methods: Twenty histopathologically confirmed oral submucous fibrosis cases were randomly selected and divided into two groups, with 10 cases in each group. Group A patients were given intralesional dexamethasone 2 ml (2 mg/ml), hyaluronidase (1500 IU), and 0.2 cc lignocaine (2%), every week. In addition, group B patients were given oral vit E capsules, 400 IU OD, for a period of 8 weeks. Weekly follow-ups were done. Results: Addition of vitamin E to the conventional treatment had synergistic effect with more improvement in the patient's condition in terms of burning sensation, vesiculation/ulceration, pigmentation, paleness of oral mucosa, tongue protrusion, and extent of mouth opening, which was confirmed histopathologically. Conclusion: Vitamin E has a significant role in the improvement of oral submucous fibrosis, which was proven in the present study.